2020
DOI: 10.15408/etk.v19i1.13772
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Responsible Investment: Concept and the Commonalities with Islamic Financial Institutions

Abstract: This paper aims to highlight the Sustainable and Responsible Investment (SRI) concept, similarities, and opportunities with Islamic financial institutions (IFIs), especially in Malaysia's perspectives. This paper is conceptual., thus the methodology used in this paper is qualitative, focusing on document analysis method by analyzing previous literature, books, reports, official website, and articles. Based on the analysis, SRIs and IFIs share the same fundamental aim, which is to utilize the funds with high mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This point is in line with studies by Mohamad et al (2016) and Wahab and Naim (2020), which found that the IFIs require careful identification and investigation of a desired outcome. By simply adopting the SRI concept, it may raise Shariah issues, that later may affect the product offerings.…”
Section: Lead To Shariah Issuessupporting
confidence: 86%
“…This point is in line with studies by Mohamad et al (2016) and Wahab and Naim (2020), which found that the IFIs require careful identification and investigation of a desired outcome. By simply adopting the SRI concept, it may raise Shariah issues, that later may affect the product offerings.…”
Section: Lead To Shariah Issuessupporting
confidence: 86%
“…One of the sharia products that attract investors is Sukuk. Sukuk has a significant potential to evolve as innovative Islamic financial instruments that obey the sharia principles (Ahmed et al, 2014;Haji Wahab & Naim, 2020;Zakaria et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this matter, issues such as the preservation of life, improvement of life quality, and preservation and promotion of mind/intellect of youth are directly related to the Dharruriyat (necessities) of Maqasid Shariah. Apart from that, the SRIs concept also denotes the principles that promote socio-economic justice, repulsion of harm, and encouragement of ethics and morality in financial practice, which aligns with Islamic principles (Wahab & Naim, 2020).…”
Section: Sris Practices Based On Maqasid Shariah and Maslahahmentioning
confidence: 99%